Context, Contextualisation and (Multimodal) Text - Gambier Yves (Lithuania, 2022)
Context and genres are relevant concepts in Translation Studies, but paradoxically there is no consensus about their definition and how they challenge text, especially after the 1990s when technology began to impact on translation practices. It is surprising since new writings and textualisation of the interactions have developed concomitant with the dematerialisation of the context. In this study, we will trace the conceptual polysemy of “context”, first in linguistics (taken in a broad meaning) and then in Translation Studies. We will consider to what extent context and contextualisation are related, when translation is defined as a context-dependent meaning-making process. What does re-contextualisation imply, and how does context apply to (multimodal) text in a digital environment?